2015
DOI: 10.3329/nimcj.v5i2.23128
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between two empirical antibiotic regime in the management of childhood malignancy with fever

Abstract: Objective : The present prospective randomized clinical trial was carried out to assess whether combined cefepime and amikacin as empirical antibiotic therapy was more effective than combined ceftriaxone and gentamicin in the treatment of febrile neutropenic children with malignant diseases. Material & Methods :The study was conducted in the Pediatric Hematology and Oncology unit of BSMMU over a period of 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Regarding to the EAT, combination of ceftriaxone and gentamycin constituted around 72% of the regimen in the current study. But comparative study at Bangabandhu Sheikh Mujib Medical University Hospital showed that empirical treatment of FN with combined cefepime and amikacin is more effective than combination of ceftriaxone and gentamicin in children with malignancies [14].Empiric antibiotic therapy with agents active on viridans group streptococci and pseudomonas aeruginosa are recommended as a standard of care in high-risk FN childhood cancer patients to provide coverage for virulent organisms while minimizing exposure to unnecessary antibiotics, because indiscriminant use of broad-spectrum antibiotics may accelerate antibiotic resistance rates [3,15]. β-lactams and aminoglycosides were the most common antibiotics used in our setup.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding to the EAT, combination of ceftriaxone and gentamycin constituted around 72% of the regimen in the current study. But comparative study at Bangabandhu Sheikh Mujib Medical University Hospital showed that empirical treatment of FN with combined cefepime and amikacin is more effective than combination of ceftriaxone and gentamicin in children with malignancies [14].Empiric antibiotic therapy with agents active on viridans group streptococci and pseudomonas aeruginosa are recommended as a standard of care in high-risk FN childhood cancer patients to provide coverage for virulent organisms while minimizing exposure to unnecessary antibiotics, because indiscriminant use of broad-spectrum antibiotics may accelerate antibiotic resistance rates [3,15]. β-lactams and aminoglycosides were the most common antibiotics used in our setup.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding to the EAT, combination of ceftriaxone and gentamycin constituted around 72% of the regimen in the current study. But comparative study at Bangabandhu Sheikh Mujib Medical University Hospital showed that empirical treatment of FN with combined cefepime and amikacin is more effective than combination of ceftriaxone and gentamicin in children with malignancies [14]. Empiric antibiotic therapy with agents active on viridans group Streptococci and Pseudomonas aeruginosa are recommended as a standard of care in high-risk FN childhood cancer patients to provide coverage for virulent organisms while minimizing exposure to unnecessary antibiotics, because indiscriminant use of broad-spectrum antibiotics may accelerate antibiotic resistance rates [3, 15].…”
Section: Discussionmentioning
confidence: 99%